Analisis Sumber Dan Penggunaan Modal Kerja Pada PT. Coca Cola Amatil Indonesia Di Semarang - Suprabawati, Paramudhita, Drs. Ma'ruf , MM (2017)
The results showed that the management of resources and the use of working capital at PT. Coca Cola Amatil Indonesia Semarang seen from the aspect of profitability in mind that there are efficiencies of total assets in generating net income and performance of their own capital to generate earnings that are efficient, so that H1 proven true. Resource management and utilization of working capital at PT. Coca Cola Amatil Indonesia Semarang from the aspects of solvency in mind that own capital is expended to ensure the debt is not efficient, because the funds needed larger and the funds needed from the assets to secure the loan increases, thereby expending assets in 2015 is not efficient to guarantee debt , so that H2 is not proven true. Resource management and utilization of working capital at PT. Coca Cola Amatil Indonesia Semarang seen from the aspect of liquidity in mind that the cost needed to guarantee debt decreased slightly, so that the company efficient in the cost of Akiva smoothly and experienced the efficient use of current assets. So that the efficient performance of the company in 2015, so the H3 proven true.